Kerentanan Sosial terhadap Penyakit Demam Berdarah Dengue (DBD) di Kelurahan Bidara Cina Jakarta Timur - Narulita, Indhy; Handawati, Rayuna; Kusumawati, Lia (Jurnal Pendidikan Geografi Undiksha, 2025)
This research aims to analyze the level of social vulnerability and determine the variables that contribute most to dengue fever in Bidara Cina Village, East Jakarta. The method used in this research is quantitative descriptive using the SoVI (Social Vulnerability Index) variable. The SoVI variables used are population density, age group 5-14 years, age group 15-44 years, poor population, number of dengue fever incidents, and higher education. The SoVI variable for each RW will have its vulnerability value calculated using the PCA (Principal Component Analysis) analysis technique and weighting and scoring will be carried out to determine the distribution of social vulnerability to dengue fever. The category of social vulnerability to dengue fever in Bidara Cina Subdistrict is divided into five categories, namely very low, low, medium, high and very high. The results of the research show that social vulnerability to dengue fever in Bidara Cina Village is in the low category. The variable that contributed most to the increase in dengue fever in Bidara Cina Village was the age group 5-14 years.